EMOTIONAL INTELLECTUAL DEVELOPMENT IN THE FUTURE SOCIAL WORKERS FOR WORK IN THE AVIATION FIELD - Петренко, Т.; Санжаровець, В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The phenomenon of emotional intelligence is recognized worldwide by an increasing number of researchers. The importance and necessity of the development of components of emotional intelligence as factors that contribute to the personal and professional growth of an individual and affect his success in life, are also indisputable. Intellectual tests, popular in the early twentieth century, are nowadays increasingly used to select job applicants or schoolchildren for the appropriate specialized classes, although they were originally designed for this purpose. There is a need for a new approach to assessing the success of a future social worker. The answer to the practical query was the concept of emotional intelligence, which is actively developing in the framework of foreign and domestic psychology. Feelings are necessary and important for human activity. Even if one tries to ignore emotions, especially in business life, they will still steer clear of the person. It is important to understand your emotions and learn to use them for professional purposes. There are no non-emotional people among the most successful leaders and managers. Quite the contrary, they all skillfully use emotions to influence and control. Emotional intelligence is the ability of a person to recognize their own and others' emotions, to use them in practice. Emotional intelligence helps a person to be successful in the team, since emotions are the only working motivation for activity. When a person knows his emotions, he sees his reality better. With emotional intelligence, we can manage emotions, which helps others to feel better. Emotional intelligence is a good way to manage relationships in a team and organization